2017
DOI: 10.7448/ias.20.2.21295
|View full text |Cite
|
Sign up to set email alerts
|

Offering pre-exposure prophylaxis for HIV prevention to pregnant and postpartum women: a clinical approach

Abstract: Introduction: HIV prevention during pregnancy and lactation is critical for both maternal and child health. Pregnancy provides a critical opportunity for clinicians to elicit women’s vulnerabilities to HIV and offer HIV testing, treatment and referral and/or comprehensive HIV prevention options for the current pregnancy, the postpartum period and safer conception options for future pregnancies. In this commentary, we review the safety of oral pre-exposure prophylaxis with tenofovir/emtricitabine in pregnant an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 71 publications
0
29
0
Order By: Relevance
“…PrEP has an important role in HIV prevention, including for pregnant and breastfeeding women [22‐25]. When adherence is maintained, PrEP – formulated as once daily tenofovir disoproxil fumarate and emtricitabine (TDF‐FTC) – has been shown to be highly effective across numerous randomized trials in women [26].…”
Section: Resultsmentioning
confidence: 99%
“…PrEP has an important role in HIV prevention, including for pregnant and breastfeeding women [22‐25]. When adherence is maintained, PrEP – formulated as once daily tenofovir disoproxil fumarate and emtricitabine (TDF‐FTC) – has been shown to be highly effective across numerous randomized trials in women [26].…”
Section: Resultsmentioning
confidence: 99%
“…Altogether, 634 liveborn infants (328 (52.0%) male, 303 (48%) female, 3 missing) were HIV exposed. 24 Table 1). The proportion of women who disclosed their HIV status to someone was 74.4%, with 66.7% disclosing to their partner/spouse.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, HIV-negative mothers who acquire infection during pregnancy risk transmitting the virus to their infants. Acute HIV infection during pregnancy or breastfeeding markedly increases the risk of MTCT of HIV [23][24][25][26]. We found that HIV transmission was four times higher in HIV-negative women who seroconverted compared to women who were HIV positive at delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Data suggest that pre-exposure prophylaxis is safe in pregnancy and breastfeeding 27 ; the Antiretroviral Pregnancy Registry finds no increased risk of birth defects from pre-exposure prophylaxis exposure 28 ; a substudy of women who became pregnant while on pre-exposure prophylaxis found no difference in pregnancy loss, preterm birth, birth defects, or 1-year growth anomalies 29 ; and a pharmacokinetic study found that pre-exposure prophylaxis was undetectable or negligible in breastfed infants’ serum. 13 These safety data should encourage health care providers to discuss and perhaps offer pre-exposure prophylaxis and other HIV prevention strategies during pregnancy with at-risk women who stand to reap tremendous benefits.…”
Section: Discussionmentioning
confidence: 99%